Economic Impact of Sustainable Forest Management Practices on the Malaysian Timber Market - Abdul Samad, Abdul Rahim (2011)
Malaysia is one of the major producing countries in global timber market. At the same time, issues relating to forests such as climate change, global warming and forest management has continued to be the Malaysian Government‟s main concern. Thus, the Malaysian Government has given its priority towards Sustainable Forest Management (SFM). It is noted that Reduced Impact Logging (RIL) option is widely known as a tool to achieve SFM. Recognising the need to strengthened the SFM, Malaysia has undertaken a critical step to reduce the annual coupe or Annual Allowable Cutting (AAC) in the country and imposed stringent criteria on harvesting operations. This step was taken to ensure the sustainable capacity of the forests and to ensure the reduction or internalisation of externalities by minimising damage from timber harvesting activities. Hence, this policy implementation has affected the volume of timber that can be extracted from the forests. It is noted that, welfare economic impacts of stakeholders in timber industry will be affected as well. This is because their interests normally require trade-offs from the environmental and natural resource concerns. Furthermore, the interests of difference stakeholders were rarely fully mutually reinforcing. Thus, the impact analysis of SFM practices on Malaysian timber market is needed. The purpose of this study is not only to carry out a timber market analysis but also to flag several scenarios that potentially arise due to SFM practices (i.e. reduction in harvested area, incremental cost of internalisation the externalities, external cost of timber harvesting operations and market access). These scenarios were incorporated into the timber market model as a platform for discussion about the possible need to revise the domestic and international supply-demand of timber as well as the welfare economic impacts of timber industry. As Malaysia have three main Forestry Department (i.e. Forestry Department of Peninsular Malaysia, Forestry Department of Sabah and Forestry Department of Sarawak), this study analysed the impact of SFM on timber market based on these three regions in Malaysia. The data related to the timber market model are annual time series basis from 1970 to 2008. A partial equilibrium model was applied in this study covering supply of timber, domestic demand of timber and export demand of timber. This study employed a system of equations technique to estimate the Malaysian three regions timber market model and to determine the timber market, followed by analising the market and welfare economic impacts which incorporates several scenarios under SFM practices into the model. Based on the estimated results from the timber market analysis, price of timber, harvested area and input cost are parameters that significantly determine the well-being of domestic timber market. The partial equilibrium model analysis shows that under the SFM practices scenarios (i.e. reduction in harvested area, incremental cost of internalisation the externalities and external cost of timber harvesting operations), the equilibrium quantity of timber and the price level decreased and increased respectively. In addition, the welfare economic impacts analysis provides an empirical evidence that there is a loss in economic welfare on the Malaysian timber industry resulting from the SFM practices. However, under the scenarios of market access, the result shows that there is a gain in economic welfare on Malaysian timber industry. Hence, this study could identify the optimum level of quantity and price of timber by incorporating several scenarios under SFM practices into the timber market model. The results show that although timber producers would suffer a reduction in economic welfare from SFM/RIL practices, several advantages (i.e. prices premium and market access) could potentially offset their losses. In addition, proactive strategies and policies from the government for upstream activities in timber sector could lessen their losses in compliance with SFM practices. Although most of scenarios under SFM practices will slump the economic welfare on Malaysian timber industry, it has enhanced the forest conservation goal of the country.